2015
DOI: 10.2105/ajph.2015.302695
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Missed Clinic Visits to Disparities in HIV Viral Load Outcomes

Abstract: Objectives We explored the contribution of missed primary HIV care visits (“no-show”) to observed disparities in virological failure (VF) among Black persons and persons with injection drug use (IDU) history. Methods We used patient-level data from 6 academic clinics, before the Centers for Disease Control and Prevention and Health Resources and Services Administration Retention in Care intervention. We employed staged multivariable logistic regression and multivariable models stratified by no-show visit fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 52 publications
4
38
0
Order By: Relevance
“…In the Veterans Affairs healthcare system, black veterans were still less likely to undergo HCV treatment compared with non-black veterans in the DAA era [34]. Similar racial disparities have been observed in the treatment of HIV infection and may in part be explained by a higher rate of missed visits among black patients in HIV care [35]. Other factors, including general mistrust of the medical system, providers, and treatments, have also been associated with lower adherence to antiretrovirals among black patients and may also be important contributors to decreased HIV engagement in care [36].…”
Section: Discussionmentioning
confidence: 99%
“…In the Veterans Affairs healthcare system, black veterans were still less likely to undergo HCV treatment compared with non-black veterans in the DAA era [34]. Similar racial disparities have been observed in the treatment of HIV infection and may in part be explained by a higher rate of missed visits among black patients in HIV care [35]. Other factors, including general mistrust of the medical system, providers, and treatments, have also been associated with lower adherence to antiretrovirals among black patients and may also be important contributors to decreased HIV engagement in care [36].…”
Section: Discussionmentioning
confidence: 99%
“…34,35 The present study contributes that this relationship may be explained by disparities in visit adherence, supporting a previous study that suggested that racial differences in engagement in care contribute to downstream clinical consequences, and this effect is mediated by visit adherence. 36 Future studies should explore the possibility that non-HIV related and intersectional stigmas (i.e., racism) contribute to these findings. 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, national racial disparities in HIV health outcomes [24, 35] may actually belie the presence of other factors. For example, in a multi-site trial, Zinski and colleagues found that the lower proportion of viral suppression found among African Americans in comparison to other racial groups loses statistical significance when accounting for the number of missed visits [36]. …”
Section: Reviewmentioning
confidence: 99%